1991
DOI: 10.1103/physrevlett.66.2621
|View full text |Cite
|
Sign up to set email alerts
|

Localized traveling-wave convection in binary-fluid mixtures

Abstract: The structure and dynamics of both subcritical and supercritical localized traveling-wave (LTW) convective states with different extensions and uniquely selected width are determined by numerical integration of the proper hydrodynamic field equations with realistic horizontal boundary conditions. A largescale mean concentration current loop influences the LTW significantly. It generates a concentration distribution that hinders propagation of the LTW pulse, so that the group velocity is small but finite.PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…The applied algorithm is based on a popular marker-and-cell-method (MAC) [39,40] extensively used to simulate thermal convection in fluids [41]. Therein the non-dimensionalized incompressible evolution equations read as (12) with u and w being the x-and z-component of the velocity, respectively and p being the pressure.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The applied algorithm is based on a popular marker-and-cell-method (MAC) [39,40] extensively used to simulate thermal convection in fluids [41]. Therein the non-dimensionalized incompressible evolution equations read as (12) with u and w being the x-and z-component of the velocity, respectively and p being the pressure.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…LTWs consist of slowly drifting, spatially confined convective regions that are embedded in the quiescent fluid. These intriguing structures have been investigated in experiments [4,5,7,10,18,27,28,29,30,31,32,33,34] and numerical simulations [14,24,26,35]. A discussion of various theoretical models aiming at their explanation is contained in Sec.…”
Section: Localized Traveling Wavesmentioning
confidence: 99%
“…This is the critical linear group velocity v g if the coefficients are derived from an asymptotic reduction of the full hydrodynamic field equations. But v g is too fast by a factor of about 20-40 compared with the LTW drift velocity in experiments or simulations [7,14,21,26,28,35,76,77,78]. Brand and Deissler [79] introduced asymmetry in the pulse properties by adding nonlinear gradient terms to the CGLE.…”
Section: E Comparison With Ltw Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[118,119] Lücke and collaborators studied pulses by the numerical integration of the Navier-Stokes equations for binary-mixture convection. [120] It has been suggested that pulses are related to the solitons of the nonlinear Schrödinger equation, modified by the dissipative contributions to the Ginzburg-Landau equation or the physical system. [121] A detailed theoretical discussion of fronts and pulses was given by van Saarloos and Hohenberg.…”
Section: The 1980'smentioning
confidence: 99%